The Impact of Strategic Leadership on Entrepreneurial Performance An Analytical Study of the Opinions of a Sample of Administrative Leaders in The Union Company for Food Industries Ltd. in Babylon (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2023)
IntroductionOur current research seeks to measure the impact of leadership with its dimensions represented by (determining direction, investing and preserving core capabilities, developing human capital, promoting culture) a questionnaire a questionnaire on all measurements at various administrative levels, the chairman of the board of directors of the company, the executive director, the general manager, and the management of departments and divisions in Union Company for Food Industries Ltd In order to process this data and test the hypotheses, the researcher used a number of statistical methods, the most important of which are (the arithmetic mean, the standard deviation, the relative coefficient of difference, and the relative importance).working methodsUsing the analytical method to reach the results through the use of the questionnaire form and subjecting it to several statistical methods and tools through the SPSS statistical analysis program.ConclusionsIt is clear from the results of testing the hypotheses of the study that there is a significant effect of the strategic leadership variable on the entrepreneurial performance at the level of the study sample company, and this indicates that the more the administrative leaderships in the study sample company pay attention to the dimensions of strategic leadership and follow strategic behaviors, the more they have an insight into the future and a vision It has a clear and deep understanding of the market dynamics, and it has the necessary expertise, skills, and capabilities to deal with environmental variables. The higher the level of entrepreneurial performance at the level of the study sample company, the greater its ability to achieve success.It was also clear from the results of testing the hypotheses of the study that there is a significant effect of the dimension of defining the strategic direction on the entrepreneurial performance, and this means that the study sample company paid more attention to defining its strategic direction clearly and formulating its strategy with high transparency, and the more its administrative leaders had a full understanding of the strategic process, the higher the performance its pioneer.The results of hypothesis testing showed that there is a significant effect of the investment dimension and the preservation of core capabilities in the entrepreneurial performance variable. Resources and expertise in order to build core capabilities and improve their outputs.From the results of testing the hypotheses of the study, it was found that there is a significant effect of the dimension of strengthening the organizational culture in the variable of entrepreneurial performance. Social, this is a matter of raising the level of his leadership performance.